Perspectives on climate change in South Asia - Amjath Babu, Tharayil Shereef; Anwar, Nausheen H.; Chanda, Abhra; Chaturvedi, Rajiv Kumar; Saadia Hina; Suvarna Fadnavis; Chaya Sarathchandra; Shree Raj Shakya; Singh, Chandni (Nature Research, 2025)
Home to roughly a quarter of the world’s population, South Asia is a hotspot for global warming impacts. In this Viewpoint, nine researchers from South Asia discuss the progress made in understanding and responding to climate change in the region.